The importance of balanced pro-inflammatory and anti-inflammatory mechanisms in diffuse lung disease - Keane, Michael P (BioMed Central, 2002)
The lung responds to a variety of insults in a remarkably consistent fashion but with inconsistent outcomes that vary from complete resolution and return to normal to the destruction of normal architecture and progressive fibrosis. Increasing evidence indicates that diffuse lung disease results from an imbalance between the pro-inflammatory and anti-inflammatory mechanisms, with a persistent imbalance that favors pro-inflammatory mediators dictating the development of chronic diffuse lung disease. This review focuses on the mediators that influence this imbalance.